2018
DOI: 10.1136/bmjopen-2017-019090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hospital admission rates for psychiatric patients cared for by multidisciplinary outreach teams with and without peer specialist: a retrospective cohort study of Japanese Outreach Model Project 2011–2014

Abstract: ObjectiveThis study examined whether having peer specialists (PS) in psychiatric multidisciplinary outreach teams was associated with a lower risk of hospitalisation, improved social functioning and decreased problem behaviours.Design and settingThis study was a retrospective cohort study based on medical records. This study was conducted as a part of the Japanese Outreach Model Project 2011–2014, which provides services for persons diagnosed mainly as ICD-10 F0, F2 and F3, who have a high possibility of hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For instance, it has been shown that peer support leads to increased self-efficacy and a lower rate of readmissions to acute care. [20][21][22][23] In addition, peer support can potentially improve recovery, 24 25 mental and physical health, 24 26 as well as quality of life, 24 reduce inpatient admissions 20 and increase the voluntary use of clinical, psychosocial and vocational support services. 27 There is also evidence that peer support is able to reduce the use of coercive measures.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…For instance, it has been shown that peer support leads to increased self-efficacy and a lower rate of readmissions to acute care. [20][21][22][23] In addition, peer support can potentially improve recovery, 24 25 mental and physical health, 24 26 as well as quality of life, 24 reduce inpatient admissions 20 and increase the voluntary use of clinical, psychosocial and vocational support services. 27 There is also evidence that peer support is able to reduce the use of coercive measures.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Also, a very small number of ACT and other programs for people with severe mental illness have been implemented in Japan, and have shown positive results in reducing psychiatric symptoms 23 and hospitalization 24 , 25 , 26 or improving functioning. 23 , 24 , 27 In particular, the services of medical support for psychiatric symptoms and assistance with daily living tasks were more common in previous studies of outreach focused mainly on people with a psychiatric diagnosis (severe mental illness) who discontinued or did not receive long‐term treatment. 26 , 27 However, these services seldom provide services to people with undiagnosed mental health problems.…”
Section: Introductionmentioning
confidence: 99%